The Uruguay Round and WTO2 - a resumé and outlook for the developing countries in agriculture - Sharma, Ramesh (2000)
Addresses two topics viz. the experience of the developing countries with the Agriculture Agreement; and what reforms would these countries be interested in seeing in the next round.